Edukasi Kesehatan Menggunakan Media Video Terhadap Pengetahuan dan Sikap Pemberian ASI Eksklusif Pada Ibu Hamil - Neneng Safitri (Jurnal Forum Kesehatan, 2019)
Low exclusive breastfeeding is a threat for growth and development of children. According to the Ministry of Health in 2018 the achievement of exclusive breastfeeding Indonesia in 2017 amounted to 35.7%, whereas in Palangka raya it amounted to 14.9%. One of factors caused the low exclusive breastfeeding are inadequate mother's knowledge and attitude. To determine effectiveness effect of the health education video to increase knowledge and attitudes of exclusive breastfeeding in third trimester pregnant women at the work area of Puskesmas Pahandut Palangka Raya. This research is a quasi experiment with control group design pre test − post test. The population and sample in this research are third trimester pregnant women at the work area of Puskesmas Pahandut Palangka Raya with 69 people used simple random sampling technique. The development of video used Thiagarajan's theory which has been validated by multimedia experts, learning experts and midwifery experts. Data collection used a questionnaire. Data analysis used General Linear Model (GLM). The results of this research showed an increase before and after the provision video with a difference of 14 points in the knowledge variable and a difference of 16 points in the attitude variable. Significantly there was an increase in knowledge using video (F = 275,727; sig = 0,00; partial eta = 0,80) and attitudes showed (F = 370,015; sig = 0,00; partial eta = 0,84).